Training for Multiple Cultures - Edmundson, Andrea; American Society for Training and Development (Info line, 2010)
The goal in training people from any culture is to provide learning opportunities that allow all learners, no matter what their native country or language, to acquire new knowledge and skills with the same effort. To accomplish this, training courses and materials must be adapted to remove any barriers created by cultural, differences within the content, approaches to training, and technologies/media used. This Infoline, focuses on how to analyze the cultural characteristics of targeted learners to determine what adaptations to the learning might be needed, recommend critical adaptations to training courses or materials and then test those recommendations, and adapt the training course to the needs of the targeted learners in the most effective way possible, with respect to effort and cost.
Keywords: Intercultural communication; Employees : Training of; Social values : Cross-cultural studies